Topography of the cephalic sensory canal system of the family Channichthyidae (Perciformes, Notothenioidei) - Iwami, Tetsuo; Matsuo, Akane; Numanami, Hideki (National Institute of Polar Research, 1999)
P(論文) Morphological peculiarities of cephalic sensory canals of 15 species of the family Channichthyidae are analyzed. Two species of the Bathy-draconidae are also studied as the sister group of the Channichthyidae. The general structural plan of the cephalic sensory canal system in the Channichthyidae is considered to be the percoid type. Some morphological variations among channichthyid species are recognized in the connection between the preoperculo-mandibular and temporal canals, the pore numbers of the infraorbital, preoperculo-mandibular and supratemporal canals, and the development of prolonged canaliculi of the infraorbital canal. In comparison with the morphological variations in the cephalic sensory canal systems of the Nototheniidae, However, those of the Channichthyidae are not so conspicuous. Relationships among some channichthyid species are discussed based on the evaluation of these morphological features. departmental bulletin paper